PARAFFINS AND POLYAROMATIC HYDROCARBONS FROM WASTE PET UNDER SLOW HEATING RATE PYROLYSIS - Ogunyemi O.I; Oyedeko K.F.K; Eruola O.A; Ricketts M. S. (IJRDO-Journal of Applied Science, 2019)
Poly Ethylene Terephthalate (PET) a polyester is one of the thermoset plasticsor synthetic fibres produced by step growth polymerization. It is in high demand world overbecause of its intrinsic properties especially for liquid substances. In Nigeria, particularly Lagos State tonnages of PET are disposed of indiscriminately as wastes unchecked thereby contributes to flooding and ecosystem to breed mosquitoes. Due to its non-biodegradablenature recyclingvia thermolytic is commonly used for its conversion to either liquid fuels or chemical feedstock. In this study local materials were used to convert waste PET via pyrolysis to obtain liquid volatile organic compounds (VOC) and solid organic compound at temperatures 90oC-124oC, which upon analysis using SRI 8610C GC-FID instrument showed that the products contained saturated paraffins (C11-C19) and poly aromatic hydrocarbons (PAHs) from simple naphthalene up to complex benzoperylene and indenopyrene. The use of local chalk or its mixture with inorganic base shows advantages over inorganic base lime for it reduces gases and little or no water formation in the course of pyrolysis.